Atributos físicos, químicos e microbiológicos do solo em sistemade integração lavoura pecuária - floresta - Marcio Neves Rodrigues (2012)
The integrated crop-livestock-forest is an important strategy for recovery of degraded areas, since they increase biodiversity and soil cover, and reduces erosion, promoting good physical and chemical conditions of the soil. The experiment was conducted at the ICA / UFMG in Montes Claros - MG in Alfissol Eutrophic and aimed to evaluate the physical, chemical and microbiological soil systems ILPF compared with other land uses. The study evaluated ILPF systems, monoculture acacia (Acacia mangium), eucalyptus (Eucalyptus urophylla x E. grandis), Brachiaria Brizantha, Brachiaria decumbens, Sorghum bicolor, Panicum maximum, with variations of cultivation in three agricultural cycles in period two years, compared to native forest, Brachiaria Brizantha with over 08 years of activity and degraded pasture of Panicum maximum with areas of exposed soil. Compared to the native forest systems and well managed pasture and IAFP, the organic matter content and soil calcium were lower in monocultures of eucalyptus, acacia and grasses. However, among the systems ILPF no significant changes in aggregate stability, the density and porosity of the soil at 27 months of its implementation. The fact that the soil has good fertility in general contributed to the variables CEC, pH, potassium and magnesium evaluated not facilitate the distinction of environments analyzed. The soil organic matter and Ca levels were higher in environments of native forest and pasture conserved, and can be considered in assessments ILPF with few years of implementation. Although not statistically differ from microbial activity in the treatment showed better results were similar when the C: N ratio of 10:1 in the soil. The content of organic matter and nitrogen influenced microbial activity and providing greater biomass.